2015
DOI: 10.2298/vsp131010036p
|View full text |Cite
|
Sign up to set email alerts
|

Specificities of transplantation of kidneys procured from donors with situs inversus totalis: A case report and review of the literature

Abstract: In donors with previously di- agnosed SIT the multidisciplinary approach, preoperative evaluation of the patient and detection of possible vascular anomalies are required to provide maximum safety for the donor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Our literature review found a total of 10 cases of donor nephrectomy in individuals with SIT [13][14][15][16][17][18][19][20] (Table 1). These cases were reported in eight different studies, with the first one being published by Black et al in 2003 [13].…”
Section: Discussionmentioning
confidence: 99%
“…Our literature review found a total of 10 cases of donor nephrectomy in individuals with SIT [13][14][15][16][17][18][19][20] (Table 1). These cases were reported in eight different studies, with the first one being published by Black et al in 2003 [13].…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports about living donations and performing laparoscopic nephrectomies, with excellent result, as it was expected. [112][113][114][115] Detailed imaging is mandatory to reveal the exact anatomy.…”
Section: Kidneymentioning
confidence: 99%